G382 Multi cystic dysplastic kidney (MCDK) disease: Do we need to perform a DMSA scan as a routine?. (27th April 2016) - Goyal, S; Krishnan, R
Abstract : Aim: To evaluate the current practices with the local guidelines particularly in relation to the usefulness of different radiological imaging in the follow up of children with Multi cystic dysplastic kidneys (MCDK) disease. Method: This was a retrospective study which included all the children diagnosed with MCDK disease from March 2005 to March 2015. To identify the patients, computerised data were looked at using ICD code Q61.4 – Renal dysplasia. The study included 32 children for whom demographic data was collected, evaluated antenatal ultrasound scan results and postnatal management. The results of follow up ultrasound scans, dimercaptosuccinic acid scans (DMSA) and micturating cystourethrograms (MCUG) were also studied. We also analysed associated other urinary tract abnormalities and complications along with discharge from the follow up. Results: All the children were managed in line with the local guidelines. There was a slight male preponderance (53%) and more common on left side (53%). All children (100%) were diagnosed antenatally. The DMSA scan was performed in 16(50%) patients and ultrasound scan in 27 (84%) patients. In 22 children (69%) postnatal ultrasound scan showed more than 50 th centile compensatory hypertrophy of the contralateral kidneys. Only 5(15%) children had vesico-ureteric reflux (ipsilateral – 2, contralateral –2, bilateral –1) and 2 (6%) had grade 4–5 reflux. Most common urinary tract abnormality noted was ipsilateral ureterocele in 5 (15%) patients and 3 (9%) children had UTI. In 10 (31%) children, MCDK completely involuted, mostly between 12–24 months of age and 16 (50%) children were discharged, mostly between 12–24 months of age. Conclusion: Although DMSA scan was performed in 50% of the children, it did not add any further clinical information in addition to the ultrasound scans. Ultrasound criteria to diagnose the MCDK is very specific and it is unlikely to be missed by an experienced and trained paediatric radiologist. DMSA scan should be done if there are doubts about the ultrasound scan results.